TRANSFORMASI RUANG RAWA KOTA BANJARMASIN - Irwan Yudha Hadinata (UNHI Press, 2021)
Banjarmasin is a marsh-based city that developed before government-controlled planning. Marsh space is the most targeted percentage of the community's habitable area beside the riverbank area. The reality of changing the utilization of swamp space from swamp farmland to residential areas makes swamp space in Banjarmasin City begin to decrease and tend to be blocked by the development of urban infrastructure. The issues raised in this study are why and how the transformation of swamp space in Banjarmasin is seen from the use of space. The purpose of this study is to find a pattern of changes in swamp space so that it can be carried out in anticipation of development, especially in the lens of sustainable development and mitigation against disasters in swamp areas. The results of this study explain that there are two general patterns in the utilization of swamps, namely the management of swamps into solid soil as a whole and swamp subsidence regulated by local regulations since 2012. The conclusion in this study explains that the utilization of swamp space can be done in development engineering efforts by paying attention to aspects of environmental quality and sustainability so that the pattern of changes in swamp space can be controlled and provide benefits for the city. The recommendations of the results of this study are: making swamp space integrated with the theme of green open space both from the scale of settlements to the scale of cities; Reconnect the swamp space under the building so that urban water flow can be managed to avoid disaster. and, make additional policies related to the coefficient of swamp space in every development effort in the city of Banjarmasin.